2009
DOI: 10.1051/0004-6361/200811590
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contamination by old main-sequence stars in young moving groups: the case of the Local Association

Abstract: Context. The associations and moving groups of young stars are excellent laboratories for investigating stellar formation in the solar neighborhood. Previous results have confirmed that a non-negligible fraction of old main-sequence stars is present in the lists of possible members of young stellar kinematic groups. A detailed study of the properties of these samples is needed to separate the young stars from old main-sequence stars with similar space motion, and identify the origin of these structures. Aims. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…West et al 2008), adding the condition of being member of a young moving group places a greater restriction on a star's age. Nevertheless, since the Montes et al (2001a) sample also contains some old stars (López-Santiago et al 2009), several stars of our present work could be older than ∼1 Gyr. The remaining 39 stars of our sample were selected because they showed a high level of magnetic activity, rotational rate, and/or lithium abundance.…”
Section: Sample Selection Observations and Data Reductionmentioning
confidence: 86%
See 4 more Smart Citations
“…West et al 2008), adding the condition of being member of a young moving group places a greater restriction on a star's age. Nevertheless, since the Montes et al (2001a) sample also contains some old stars (López-Santiago et al 2009), several stars of our present work could be older than ∼1 Gyr. The remaining 39 stars of our sample were selected because they showed a high level of magnetic activity, rotational rate, and/or lithium abundance.…”
Section: Sample Selection Observations and Data Reductionmentioning
confidence: 86%
“…In a recent work, López-Santiago et al (2009) demonstrated that the sample of possible members of the young stellar kinematic groups of Montes et al (2001a) is partially contaminated by active field stars that do not belong to the moving groups. In that work, the stars in the X-ray saturation regime also showed high Hα fluxes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations